Black and white Manhattan the history of racial formation in New York City, 1624-1783 - Foote, Thelma Wills, 1956- (Oxford University Press, 2003)
Probing the colonial history of New York City, Thelma Foote examines the broadly shared belief that black slavery and antiblack racism were marginal to the experience of northern colonies in British North America.